Penerapan Hygiene Sanitasi Di Rumah Makan Minang Simpang Ampek Panjer Kota Denpasar Tahun 2021 - Dewi Puspita Sari; I Nyoman Gede Suyasa (Poltekkes Kemenkes Denpasar, 2021)
A restaurant is one of the places visited by the general public with special attention in the field of sanitation. Based on preliminary observations made by some food handlers, they do not use plastic gloves when processing food. This study aims to see the state of sanitation hygiene in the Minang Simpang Ampek Panjer Restaurant, Denpasar City. The type of research used is descriptive research with a survey method. Observation results show that the selection of food ingredients produced is 100%. 100% food processing. Storage of 100% foodstuffs. 100% finished food storage. Serving 80% of the production. 80% personal hygiene result. The application of cleanliness as a result of the calculation meets the requirements, namely 93.33%. Food handlers should use plastic gloves when processing food. Serving food should use a food cover so that food is not contaminated with dust, insects, hair or other dirt. Food packaging should use food grade or health-safe packaging such as using banana leaves when wrapping food